1999
DOI: 10.1093/oxfordjournals.jpart.a024418
|View full text |Cite
|
Sign up to set email alerts
|

Are Women More Ethical? Recent Findings on the Effects of Gender Upon Moral Development

Abstract: Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission. JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 24 publications
2
43
0
2
Order By: Relevance
“…Similar findings, indicating greater ethical sensitivity of women over men, are also reported by Deshpande et al (2006), Erdener (1996), Kelly et al (1990), Kohut and Corriher (2001), Lopez et al (2005), Stevenson and Bodkin (1996), and White (1999). However, none of the research cited controlled for the possible confounding effects of variables that might covary with sex and ethical attitudes or behavior.…”
Section: Individual Antecedentssupporting
confidence: 59%
“…Similar findings, indicating greater ethical sensitivity of women over men, are also reported by Deshpande et al (2006), Erdener (1996), Kelly et al (1990), Kohut and Corriher (2001), Lopez et al (2005), Stevenson and Bodkin (1996), and White (1999). However, none of the research cited controlled for the possible confounding effects of variables that might covary with sex and ethical attitudes or behavior.…”
Section: Individual Antecedentssupporting
confidence: 59%
“…This last reason concurs with other studies (for example Awdry & Sarre, 2013) where females reported that their plagiarism was unintentional compared to male students who said they had intentionally plagiarized their work (7 % versus 1 % of females). Other suggested explanations can be found in studies on gender difference in cognitive moral development (Gilligan 1982;Kohlberg 1973) and motivation/intentions related to unethical behavior (Colnerud and Rosander 2009;Tibbetts 1999;White 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been heavy criticism that Kohlberg's theory of moral development is gender-biased (Gilligan, 1982), there has been no empirical support to back those claims. There has actually been evidence that the claim of gender-bias is inaccurate (Green & Maccoby, 1986;Walker, 1984;White, 1999). Kohlberg's theory still survives as seemingly the predominant theory of moral development.…”
Section: Resultsmentioning
confidence: 99%
“…White (1999), using the MJI, actually found that female members of the u.S. Coast Guard scored higher than their male counterparts on measures of moral judgment, again providing research that does not support Gilligan's claim of gender-bias. Critics of Gilligan state that the open-ended interview technique employed during her research left for extensive interpretation of the answers by the researcher, allowing for bias (Colby & Damon, 1983).…”
Section: Moral Developmentmentioning
confidence: 90%